Effect of Nonlinear Factors on Typhoon-Induced Storm Surges - Fanjun Chen; Kaixuan Ding; Zhilin Sun (Journal of Marine Science and Engineering)
This study employs the Delft3D numerical model to elucidate nonlinear interactions in velocity dynamics across four key marine regions during typhoon-induced storm surges (Typhoon In-fa, No. 2106). To address gaps in understanding how typhoon winds drive storm surges, this study aims to analyze the relative contributions of bottom friction, wind stress, and convective terms to storm surge dynamics, providing insights for predictive modeling and marine hazard mitigation. Introducing a novel metric, the “Flow Velocity Nonlinear Coupling Proportion” (“FVNCP”, abbreviated as “NCP”), this research quantifies the interactive effects of storm surge flow velocity by dissecting the contributions of bottom friction, wind stress, and the convective term. Through decision tree modeling, wind stress emerges as the primary driver of NCP in open sea and sheltered areas, with peak values reaching 1.50 × 10−4 and 2.14 × 10−4 m/s2, respectively. In contrast, the convective term dominates the strait and bypassing regions, exhibiting maximum impacts of 3.21 × 10−4 and 2.94 × 10−4 m/s2, while bottom friction’s influence is consistently minor across all regions. Wind stress contributes the most to NCP in open waters, at an average of 48.28%, while the convective term exerts a comparable 38.85% effect. In confined areas like the strait and bypassing regions, the convective term accounts for 40–44% of the NCP, with wind stress contributing 32–39%. The role of bottom friction is the least among the three factors though its impact intensifies in shallower zones. These findings offer critical insights for advancing predictive models and informing strategies to mitigate typhoon-driven marine hazards.